2018
DOI: 10.1186/s13673-018-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of online interpersonal interaction on purchase intention based on stimulus-organism-reaction model

Abstract: Background On January 31, 2018, the China Internet Network Information Center (CNNIC) released the 41st Statistical Report on China's Internet Development in Beijing. By December 2017, the number of Internet users in China reached 772 million, accounting for 55.8% of the total population, which exceeds the global average (51.7%) by 4.1% and the Asian average (46.7%) by 9.1%. The rapid development of digital technology and Internet has changed the traditional model of interpersonal interaction. The "Hyperperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…The results are in accordance with previous researchs conducted by [10], [15], [16], [17], [18], [19], [20], [21], that online consumer behavior variable has a positif and significant effect on Online Purchase Intention.…”
Section: Discussion 1) the Influence Of Online Consumer Behavior On supporting
confidence: 92%
“…The results are in accordance with previous researchs conducted by [10], [15], [16], [17], [18], [19], [20], [21], that online consumer behavior variable has a positif and significant effect on Online Purchase Intention.…”
Section: Discussion 1) the Influence Of Online Consumer Behavior On supporting
confidence: 92%
“…This will result in a positive or negative behavioral outcome (response) (Mehrabian & Russell, 1974 ). More specifically, a stimulus is an influencing variable of the external environment that can exert influence on the person’s cognitive, mental, and emotional state (Liu et al, 2018 ). This will then be manifested as an active response to external stimuli in terms of the person’s specific behavior (Kamboj et al, 2018 ; Zhu et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building customer trust has always been challenging for s-commerce retailers. Multiple studies examining online commerce have identified trust as a catalyst in building customer relationship (Hollebeek and Macky, 2019;Liu, Luo and Cao, 2018;Ofori et al, 2017). By minimizing complexity and perceived risk, trust motivates customers to engage with retailers (Lu et al, 2016).…”
Section: Hypothesis Formulationmentioning
confidence: 99%
“…According to Stephen and Toubia (2010, p. 15), s-commerce represents "forms of internet-based social media that allow people to participate actively in marketing and selling of products in online marketplaces and communities." S-commerce is an amalgamation of different online marketing strategies, online retail environment and consumers' responses (Fang et al, 2018;Liu, Luo and Cao, 2018;Islam and Rahman, 2017). Given such theoretical basis, four s-commerce cues are constructed as stimulus, while customer engagement and repurchase intention are constructed as organism and response, respectively.…”
Section: Introductionmentioning
confidence: 99%